Effect of maintaining apical patency on endodontic pain in posterior teeth with pulp necrosis and apical periodontitis: a randomized controlled trial. (28th April 2015) - Arora, M.; Sangwan, P.; Tewari, S.; Duhan, J.
Abstract: Aim: To evaluate the association between apical patency and post‐operative pain in posterior teeth with pulp necrosis and apical periodontitis. Methodology: Sixty‐eight patients requiring primary root canal treatment in mandibular first molars with necrotic pulps and apical periodontitis were included. The patients were randomly allocated to one of two groups: patency ( n  = 34) and nonpatency ( n  = 34). After administering local anaesthesia, root canal preparation was completed using ProTaper rotary instruments. A size 10 K‐file was used as a patency file and carried 1 mm beyond the working length (WL) between each instrument change in the patency group, while it was carried up to WL in the nonpatency group. Patients were asked to record their pain experience on a pain chart daily for 7 days. Three patients (two in the patency group, one in the nonpatency group) did not return with completed pain charts on the subsequent visit, resulting in a total of 65 patients for the final analysis (patency, n  = 32; nonpatency, n  = 33). Data was analysed using Chi Square test, t ‐test, Mann–Whitney test and Wilcoxon Signed Ranks test. Results: Overall, 43% of the patients experienced post‐operative pain. The patency group had less incidence of pain (34%) as compared to the nonpatency group (52%), but the difference was not significant ( P  = 0.163). Conclusion: Maintenance of apical patency during chemomechanical preparation had no significant influence on post‐operative pain in posterior teeth with necrotic pulps and apical periodontitis.